Fostering Critical Thinking Skills through Project-Based Learning and Learning Motivation in Local History Education - Ilmiawan; Anas Mundandar; Dian Eka Mayasari Sri Wahyuni (Jurnal Pedagogi dan Pembelajaran, 2026)
Developing students' critical thinking skills remains a major challenge in higher education history learning, particularly due to the dominance of teacher-centered instruction and limited attention to learning motivation. This condition results in superficial understanding and low levels of higher-order cognitive engagement. Therefore, this study aims to analyze and evaluate the contribution of Project-Based Learning (PjBL) and learning motivation to the enhancement of students’ critical thinking skills in local history education. The study involved 71 undergraduate students enrolled in a history education program. Data were collected through critical thinking skills tests, learning motivation questionnaires, and classroom observation sheets to examine the implementation of PjBL. All instruments were validated by experts prior to use. Data analysis was conducted using descriptive statistics and inferential analysis, including paired samples t-test, independent samples t-test, Mixed Between-Within ANOVA, and linear regression analysis. The results indicate a significant improvement in students’ critical thinking skills after the implementation of PjBL, with students in the project-based learning group demonstrating substantially higher gains than those in conventional learning settings. Furthermore, learning motivation was found to make a significant contribution to students’ critical thinking performance, confirming its complementary role in strengthening learning outcomes. In conclusion, integrating Project-Based Learning with learning motivation effectively fosters students’ critical thinking skills. These findings imply that educators should design learning environments that combine authentic projects with motivational support to promote higher-order thinking in history education.